Development and Characterization of Embryonic Stemlike Cell Culture from Carassius auratas (Linnaeus, 1758) - Kumar, Abhay; Kanyal, Pooja; Bedekar, Megha K.; Kumar, A. Pavan; Sushila, N.; Tripathi, Gayatri (Fishery Technology, 2017)
Embryonic stem cells are pluripotent cells, capableof differentiating into various cell types. In thepresent study, feeder cell-free culture of midblastulaembryos of the Goldfish (Carassius auratus)was carried out. Embryonic stem cells were derivedfrom mid-blastula stage embryos using pronase torelease the inner cell mass (ICM). The cells werecultured in Leibovitz-15 medium on gelatin-coatedcell culture well plates supplemented with 15% fetalbovine serum, 1% goldfish serum, basic fibroblastgrowth factor and leukaemia inhibitory factors (LIF)and were incubated at 28Â°C. The ES-like cells werecharacterized by their unique round and polygonalmorphology, elevated activity of alkaline phosphatase,spherical three-dimensional embryoid bodyformation, chromosomal diploid number (2n=50).The expression of Oct4, a member Oct family ofPOU transcription factors, which play a key role inregulating stem cell pluripotency and differentiation,was used for characterization of undifferentiatedpluripotent ES cells. The expression of Oct4 inembryonic stem-like cell (2nd passage) and gonadsof goldfish was studied by RT- PCR. Embryonicstem-like cells culture from the mid blastula embryoof C. auratus would be a useful tool for cellulardevelopment and differentiation studies.